1995
DOI: 10.1073/pnas.92.6.2012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene, spoIIR, that links the activation of sigma E to the transcriptional activity of sigma F during sporulation in Bacillus subtilis.

Abstract: Sporulation of Bacillus subtilis involves an asymmetric cell division that gives rise to two different types of cells-the larger mother cell, which is required for the formation of the spore but lyses upon its completion, and the smaller forespore cell, destined to become the spore. The fates of the two cells are controlled by separate genetic programs. However, these programs are not independent. Rather, a cascade of crossregulatory events exists to coordinate the programs (1). This cascade starts with the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
142
1
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(150 citation statements)
references
References 30 publications
(39 reference statements)
5
142
1
1
Order By: Relevance
“…8). As the spoIIR promoter is very efficiently recognized by this mutated form of F (Karow et al, 1995;Londoñ o-Vallejo and Stragier, 1995), it was substituted for the spoIIQ promoter at the spoIIQ locus (see the Experimental procedures for details of construction), which fully restored spoIIQ expression in the spoIIAC561 background (Fig. 8).…”
Section: Role Of Forespore and Mother Cell In Engulfmentmentioning
confidence: 99%
See 1 more Smart Citation
“…8). As the spoIIR promoter is very efficiently recognized by this mutated form of F (Karow et al, 1995;Londoñ o-Vallejo and Stragier, 1995), it was substituted for the spoIIQ promoter at the spoIIQ locus (see the Experimental procedures for details of construction), which fully restored spoIIQ expression in the spoIIAC561 background (Fig. 8).…”
Section: Role Of Forespore and Mother Cell In Engulfmentmentioning
confidence: 99%
“…No mutation in genes belonging to the E regulon has been isolated that leads to a similar stage of blockage and that could identify the gene(s) encoding the enzyme(s) necessary for initiating degradation of the peptidoglycan at the centre of the sporulation septum. As activation of E requires the presence of active F (Karow et al, 1995;Londoñ o-Vallejo and Stragier, 1995;Shazand et al, 1995) it is not known whether E is sufficient for inducing this morphological transition, but it is evidently required. Three loci have been identified in which mutations arrest sporulation at stage IIii: spoIID, spoIIM and spoIIP.…”
Section: Introductionmentioning
confidence: 99%
“…When grown in sporulation conditions and examined by phase-contrast microscopy, the csfX mutant was found to accumulate disporic forms, a feature characteristic of the absence of (r E activity (Lewis et al 1994; not shown). Mutations in the same locus have been obtained independently by screening for clones displaying (rF but no (r E activity (Karow et al 1995). …”
Section: The Csfx Protein Is Required For Pro-o ~ Processingmentioning
confidence: 99%
“…The activation of the different sigma factors is itself strongly coupled to specific points in the morphological sequence (45). E , for example, is synthesized in a pro-form in the predivisional cell (32,42), and its proteolytic activation is somehow coupled to the septation process and to the activity of F , a prespore-specific sigma factor (35,44). Conversion of pro-E to its active form, E , which occurs exclusively in the mother cell, inaugurates the program of gene expression in this compartment (19,35,44,68).…”
mentioning
confidence: 99%
“…E , for example, is synthesized in a pro-form in the predivisional cell (32,42), and its proteolytic activation is somehow coupled to the septation process and to the activity of F , a prespore-specific sigma factor (35,44). Conversion of pro-E to its active form, E , which occurs exclusively in the mother cell, inaugurates the program of gene expression in this compartment (19,35,44,68). The E form of RNA polymerase (E E ) directs the transcription of a heterogeneous group of genes controlling functions as diverse as engulfment (23,56,58,62), germination (49,70), cortex synthesis (2,9,14,43,52,54,60,64), and coat morphogenesis (3,18,28,49,54,60,70), as well as genes that may assist in the control of the metabolic state of the mother cell (7,8,26,37).…”
mentioning
confidence: 99%